Storage and Transmission Capacity Requirements of a Remote Solar Power Generation System - Chen, Yue; Wei, Wei; Wang, Cheng; Shafie-khah, Miadreza; Catalão, João P. S. (IEEE, 2022)
Large solar power stations are usually located in remote areas and connect to the main grid via a long transmission line. The energy storage unit is deployed locally with the solar plant to smooth its output. Capacities of the grid-connection transmission line and the energy storage unit have a significant impact on the utilization rate of solar energy, as well as the investment cost. This article characterizes the feasible set of capacity parameters under a given solar spillage rate and a fixed investment budget. A linear programming-based projection algorithm is proposed to obtain such a feasible set, offering valuable references for system planning and policy making.
Keywords: Energy storage unit; polyhedral projection algorithm; renewable power spillage; transmission line; fi=Sähkötekniikka|en=Electrical Engineering|